2022
DOI: 10.3390/ijerph191912043
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Quality of Life of University Students: A Cross-Sectional Study

Abstract: Quality of life (QOL) is a complex and multifaceted concept that has been used to study different aspects of people’s lives, including physical and psychological wellbeing, financial independence, social relationships, personal beliefs and living situation. In this study, we aimed to assess the QOL of a group of Spanish university students and identify associated factors. Method: We completed a cross-sectional study of the QOL of 868 university students using the WHOQOL-BREF questionnaire. In addition, data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 74 publications
1
14
0
1
Order By: Relevance
“…However, students in this study reported lower scores on the subscales of psychological and physical domains in the WHOQOL-BREF compared with previous national studies [46,47]. Based on the overall picture provided in the literature, there is an urgent need to incorporate health promotion programs and interventions into education to balance university students' academic achievement and overall well-being [34,45]. School administrators and faculty members need to explore barriers and start initiatives that focus on raising awareness regarding the importance of healthy lifestyle behaviors among university students.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, students in this study reported lower scores on the subscales of psychological and physical domains in the WHOQOL-BREF compared with previous national studies [46,47]. Based on the overall picture provided in the literature, there is an urgent need to incorporate health promotion programs and interventions into education to balance university students' academic achievement and overall well-being [34,45]. School administrators and faculty members need to explore barriers and start initiatives that focus on raising awareness regarding the importance of healthy lifestyle behaviors among university students.…”
Section: Discussionmentioning
confidence: 67%
“…The current findings offer pertinent data for decisionmakers who want to put strategies in place to find physical, psychological, social, and environmental obstacles to improve university students' health promotion practices and total QOL [45]. In this context, implementing programs aimed at enhancing socialization and physical health, creating health education initiatives to change students' unhealthy lifestyle choices, and preparing educators to recognize the immediate psychological needs of university students would all be significant and effective ways to enhance the QOL of university students [34,45].…”
Section: Discussionmentioning
confidence: 95%
“…Physical wellbeing is a healthy habit that must not be forgotten by university students of any area [ 24 ]. Is well known that during the higher education period, there is a multitude of important phases of development (physical, psychological, social, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Is well known that during the higher education period, there is a multitude of important phases of development (physical, psychological, social, etc.) that could affect different academic career chapters of the students, such as competition between peers, the amount of academic work or changes in living conditions [ 24 , 25 ]. Moreover, Ghassab-Abdollahi et al [ 26 ] emphasised the students’ low level of quality of life due to several factors, such as satisfaction with their studies [ 27 ], physical activity level [ 28 ], social relationships [ 29 ] and emotional wellbeing [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation